Efficacy of 4% tulsi leaf extract, fluoridated and placebo dentifrices against salivary Streptococcus mutans count among 14-15 years school children in Davangere City, Karnataka - A concurrent parallel trial - G V Usha; Nagesh Lakshminarayan; N G Bhuvaneshwari (Wolters Kluwer Medknow Publications, 2021)
Background: Dental caries is a multifactorial disease, which is preventable by adopting healthy behaviors like toothbrushing. Tulsi extract mouthrinse has confirmed its antibacterial efficacy against Streptococcus mutans. Aim: The aim of this study was to assess and compare the antibacterial efficacy of 4% tulsi leaf extract, commercially available fluoridated (Colgate Total Care), and placebo dentifrices on salivary S. mutans counts among 14-15-year-old schoolchildren in Davangere city. Subjects and Methods: A triple-blinded randomized controlled trial consisted of 84 randomly selected participants aged 14-15 years. Baseline unstimulated 2-ml saliva was collected and the microorganisms were cultured using mitis salivarius selective media. The participants with 105 colony-forming units were considered eligible. Block randomization and concealed randomization method was adopted to allocate the participants into three groups containing 28 each. After 7 days, postassessment of salivary S. mutans count was done. Statistical Analysis: Wilcoxon signed-rank test for within-group comparison and Kruskal-Wallis analysis of variance for intergroup comparison were used. Missing data analysis was performed. Results: The study showed a significant reduction in salivary S. mutans counts from baseline to posttest (mean rank 37.95-28.45) in tulsi toothpaste group. Intergroup comparison showed a statistically significant difference (P = 0.035). Post hoc analysis showed a statistically significant difference between tulsi and placebo toothpaste group (P < 0.05). Conclusion: Four percent tulsi extract incorporated in the form of toothpastes have shown a maximum reduction in the salivary S. mutans count for a period of 7 days when compared to fluoridated toothpaste.